Cognitive Distortions Associated with Imagination of the Thin Ideal: Validation of the Thought-Shape Fusion Body Questionnaire (TSF-B) - Wyssen, Andrea; Debbeler, Luka J.; Meyer, Andrea H.; Coelho, Jennifer S.; Humbel, Nadine; Schuck, Kathrin; Lennertz, Julia; Messerli-Bürgy, Nadine; Biedert, Esther; Trier, Stephan N.; Isenschmid, Bettina; Milos, Gabriella; et al. (Frontiers in Psychology, 2017)
ABSTRACT Thought-shape fusion (TSF) describes the experience of body-related cognitive distortions associated with eating disorder (ED) pathology. In the laboratory TSF has been activated by thoughts about fattening/forbidden foods and thin ideals. This study aims at validating a questionnaire to assess the trait susceptibility to TSF (i.e. body-related cognitive distortions) associated with the imagination of thin ideals, and developing an adapted version of the original TSF trait questionnaire, the Thought-Shape Fusion Body Questionnaire (TSF-B). Healthy control women (HC, n=317) and women diagnosed with subthreshold and clinical EDs (n=243) completed an online-questionnaire. The factor structure of the TSF-B questionnaire was examined using exploratory (EFA) and subsequent confirmatory factor analysis (CFA). EFA pointed to a two-factor solution, confirmed by CFA. Subscale 1 was named Imagination of thin ideals, containing five items referring to the imagination of female thin ideals. Subscale 2 was named Striving for own thin ideal, with seven items about pursuing/abandoning attempts to reach one’s own thin ideal. The total scale and both subscales showed good convergent validity, excellent reliability, and good ability to discriminate between individuals with subthreshold/clinical EDs and HCs. Results indicate that cognitive distortions are also related to the imagination of thin ideals, and are associated with ED pathology. With two subscales, the TSF-B trait questionnaire appropriately measures this construct. Future studies should clarify whether TSF-B is predictive for the development and course of EDs. Assessing cognitive distortions with the TSF-B questionnaire could improve understanding of EDs and stimulate the development of cognitively-oriented interventions.